Cloud Computing : A Practical Approach - Velte, Anthony T. (McGraw-Hill, 2010)
Contents: cloud computing basics; your organization and cloud computing; cloud computing with the Titans; the business case for going to the cloud; hardware and infrsdtructure; accessing the cloud;...